CONSTANT DRIPPING WEARS AWAY A STONE. HOW HEIKKI E. S. MATTILA ESTABLISHED COMPARATIVE LEGAL LINGUISTICS - Galdia, Marcus (Comparative Legilinguistics, 2022)
This article describes Heikki E.S. Mattila’s achievements in the area of comparative legal linguistics. It concentrates on the process of emergence of basic conceptual structure in Mattila’s work. Its further expansion and methodological requirements established by the founder of comparative legal linguistics are analyzed as well. Particularly, the establishing of Comparative Legal Linguistics as teaching subject is scrutinized from the methodological perspective that is based on interdisciplinarity. Likewise, possibilities for expansion of the conceptual structure of the newly established area of knowledge are discussed as well.